Exploration of the Historical Value of Islamic Civilization at the Baiturrahman Grand Mosque as a Source of Learning Local History in Banyuwangi - Desi Fitriani (JUSPI (Jurnal Sejarah Peradaban Islam), 2022)
The Baiturrahman Grand Mosque is one of the historical heritages of the Banyuwangi Regency, which has historical values in it. This mosque is proof of the spread of Islam in the eastern region of Java. Because it contains historical values related to establishing the Banyuwangi Regency, this mosque can be used as a source of local history learning for high school students because learning will be more interesting if you invite students directly to historical places or sites. This study uses a historical method with four stages: heuristics, criticism, interpretation, and historiography. The aims of this research are: 1) to find out the history of the establishment of the Baiturrahman Grand Mosque; 2) to find out the meaning contained in the mosque decoration; and 3) to find out the right learning model in utilizing the Baiturrahman Grand Mosque as a source of learning local history. The results of this study are in the form of a description of the historical value of the Baiturrahman Grand Mosque and a description of the meaning contained in its decoration. The next result is that this mosque is suitable to be used as a source of learning history with the 2013 curriculum, which emphasizes student skills and direct learning.